2016
DOI: 10.3390/molecules21030276
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Bioactivities of Novel Pyrazole Oxime Derivatives Containing a 5-Trifluoromethylpyridyl Moiety

Abstract: Abstract:In this study, in order to find novel biologically active pyrazole oxime compounds, a series of pyrazole oxime derivatives containing a 5-trifluoromethylpyridyl moiety were synthesized. Preliminary bioassays indicated that most title compounds were found to display good to excellent acaricidal activity against Tetranychus cinnabarinus at a concentration of 200 µg/mL, and some designed compounds still showed excellent acaricidal activity against Tetranychus cinnabarinus at the concentration of 10 µg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…Of the 24 oxime ethers obtained,1 1a re new compounds that are not described elsewhere in the literature. 1 Ha nd 13 CNMR analyses confirmed the structure of the final product. All compounds were obtained in ap ure form, which was also confirmed by the NMR spectra.M ass spectra analysis confirmed the presence of the appropriate products.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Of the 24 oxime ethers obtained,1 1a re new compounds that are not described elsewhere in the literature. 1 Ha nd 13 CNMR analyses confirmed the structure of the final product. All compounds were obtained in ap ure form, which was also confirmed by the NMR spectra.M ass spectra analysis confirmed the presence of the appropriate products.…”
Section: Resultsmentioning
confidence: 68%
“…They are used in organic synthesis, providing valuable reagentst oo btain cis-1.2-aminoalcohols, [1] hydroxyloamines, [2] enantioselectives ynthesis of the amines, [3] and,u nder specific conditions in cyclization reactions, can lead to the formation of substituted heteroaromatic compounds. [4,5] However,m any oxime ethers are applicable as specifiedc ompounds with biological activity.T hey exhibit anticancer, [6] anti-aggregation, [7] antidepressant, [8,9] anticonvulsant, [10] antimicrobial, [11] antiviral, [12] acaricidal, [13] anti-protozoal, [14] and herbicidal [15] effects. There has also been research performed on the use of oxime ethers as fragrances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Oxime ethers are interesting compounds due to their diverse biological activities. The compounds exhibit anticancer, 5 anticonvulsant, 6 antimicrobial, 7 antiparasitic 8 and acaricidal 9 activities. The most popular compound that contains oxime ether group is an oxiconazole ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that they exhibit various biological activities that are often related to low toxicity and increase a great amount of beneficial influences on human health. Therefore, they have attracted wide interest for decades owing to their diverse biological properties such as insecticidal [1], acaricidal [2], antitumor [3][4][5], fungicidal [6], antiviral [7,8], antibacterial [9][10][11], COX inhibitory [12], and fluorescent [13,14] properties.…”
Section: Introductionmentioning
confidence: 99%